MOTOR PROFILE OF CHILDREN WITH AUTISM SPECTRUM DISORDER AFTER EIGHT WEEKS OF PSYCHOMOTOR STIMULATION - Dias, Julia Muniz; Delazari, Sulamita Melo; Pereira, Eveline Torres; Diniz, Elizângela (UNESP, 2020)
About 70 million people have autism spectrum disorder (ASD) in the world. Children with this disorder have a delay in motor development. In this sense, the objective of the  study was to evaluate the motor profile of children with ASD before and after eight weeks of psychomotor intervention in Ubá city, Minas Gerais state. For this, we employed the Motor Development Scale (EDM), as a data collection instrument. Four children diagnosed with ASD, aged between six and nine years, participated in this study. They were evaluated at two times before and after the eight-week psychomotor stimulation program. The results indicated that although there was an increase in the general motor quotient of two participants, however, these were not sufficient to change the motor profile classification. Received on: 02/02/2020 Reformuleted on: 02/07/2020 Accepted: 02/10/2020